2005
DOI: 10.1177/153537020523001012
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hyperglycemia Induced by Ketamine/Xylazine Anesthesia in Rats: Mechanisms and Implications for Preclinical Models

Abstract: The effects of anesthetic agents, commonly used in animal models, on blood glucose levels in fed and fasted rats were investigated. In fed Sprague-Dawley rats, ketamine (100 mg/kg)/xylazine (10 mg/kg) (KX) produced acute hyperglycemia (blood glucose 178.4 +/- 8.0 mg/dl) within 20 min. The baseline blood glucose levels (104.8 +/- 5.7 mg/dl) reached maximum levels (291.7 +/- 23.8 mg/dl) at 120 min. Ketamine alone did not elevate glucose levels in fed rats. Isoflurane also produced acute hyperglycemia similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
185
3
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(213 citation statements)
references
References 31 publications
17
185
3
4
Order By: Relevance
“…The global ischemia model used in this study was complicated by transient, statistically equivalent intraoperative hyperglycemia in all experimental groups. This was observed shortly after induction of general anesthesia, and was likely a result of the anesthetic combination used in this study (Ketamine and Xylazine) (Kawai et al, 1997, Saha et al, 2005. Hyperglycemia may have exacerbated blood-brain-barrier breakdown during global ischemia (Dietrich et al, 1993) or possibly increased neuron loss, although we did not study these effects specifically.…”
Section: Discussionmentioning
confidence: 97%
“…The global ischemia model used in this study was complicated by transient, statistically equivalent intraoperative hyperglycemia in all experimental groups. This was observed shortly after induction of general anesthesia, and was likely a result of the anesthetic combination used in this study (Ketamine and Xylazine) (Kawai et al, 1997, Saha et al, 2005. Hyperglycemia may have exacerbated blood-brain-barrier breakdown during global ischemia (Dietrich et al, 1993) or possibly increased neuron loss, although we did not study these effects specifically.…”
Section: Discussionmentioning
confidence: 97%
“…In a rat study by Saha et al., ketamine alone did not alter BG levels (Saha et al. 2005), and they concluded that xylazine must be the BG increasing factor. Saha et al.…”
Section: Discussionmentioning
confidence: 99%
“…2005; Saha et al. 2005; Rodrigues et al. 2006); (3) the volatile agent isoflurane increases BG and some have noted a decrease in insulin concentration (Pomplun et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hyperglycemic response has been observed in several studies using isoflurane (Lattermann et al, 2001;Saha et al, 2005)) potentially due to impaired glucose clearance and increased glucose production. It is important to stress that although there was a significant difference in blood glucose level between the two groups, all animals remained normoglycemic; therefore an effect of glucose on infarct size or outcome is unlikely.…”
Section: Discussionmentioning
confidence: 99%